2019
DOI: 10.3390/su11051437
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intentions of Business and Economics Students in Germany and Cyprus: A Cross-Cultural Comparison

Abstract: The World Economic Forum in Davos suggested that promoting entrepreneurship could be a solution to the problem of youth employment, which is a serious issue with 75 million young people out of work around the world. The entrepreneurial decisions of young people are especially important in regions where economic opportunities are restricted and people choose to move from that region. Two of such regions are East Germany and Northern Cyprus. In this article, the authors are interested in analyzing entrepreneuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
2
19
0
1
Order By: Relevance
“…Our results aligned with those obtained in other countries, such as those from the study of Kaya et al [72] with German university students. These authors found that both the entrepreneurship support culture and the teaching of skills related to self-management increase the odds of future entrepreneurial activity, which reinforces the need to teach the entrepreneurial competencies in an academic environment [72]. Similarly, other studies with European and Turkish students found that entrepreneurial education is a relevant factor for providing young students with the necessary skills to act [73,74].…”
Section: Discussionsupporting
confidence: 93%
“…Our results aligned with those obtained in other countries, such as those from the study of Kaya et al [72] with German university students. These authors found that both the entrepreneurship support culture and the teaching of skills related to self-management increase the odds of future entrepreneurial activity, which reinforces the need to teach the entrepreneurial competencies in an academic environment [72]. Similarly, other studies with European and Turkish students found that entrepreneurial education is a relevant factor for providing young students with the necessary skills to act [73,74].…”
Section: Discussionsupporting
confidence: 93%
“…In scientific literature, the concept took a similar trajectory, as Godin also recounts in detail [25]. Accordingly, recent scientific literature on innovation focuses on exploring details of how innovation works, accepting as a given that it is a desirable or simply existing goal (see e.g., [20,[27][28][29][30][31][32]). Several renowned academic journals have "innovation" in their titles (e.g., the Journal of Innovation & Knowledge, the Journal of Innovation and Entrepreneurship, Innovation, and many others).…”
Section: Historical and Scientific Background Of Innovation In The Eumentioning
confidence: 99%
“…The authors conclude that generation Z is not a mere reincarnation of generations Y and X. Regarding their entrepreneurial intentions, Mahmood, Lateef, & Paracha (2020) focus on a sample of Pakistani youth from generation Z, whereas Kaya, Erkut, & Thierbach (2019) focus on samples of East German and Cyprus Turkish youngsters from generation Z; both set of authors find out that generation Z has a strong entrepreneurial intention. Kaya, Erkut, & Thierbach (2019) indicate that generation Z is very sensitive to social problems.…”
Section: Generation Z's Perspectivesmentioning
confidence: 99%
“…Regarding their entrepreneurial intentions, Mahmood, Lateef, & Paracha (2020) focus on a sample of Pakistani youth from generation Z, whereas Kaya, Erkut, & Thierbach (2019) focus on samples of East German and Cyprus Turkish youngsters from generation Z; both set of authors find out that generation Z has a strong entrepreneurial intention. Kaya, Erkut, & Thierbach (2019) indicate that generation Z is very sensitive to social problems. Mahmood, Lateef, & Paracha (2020) highlight that social pressures cannot be considered as a significant factor contributing to the entrepreneurial intentions of generation Z. Meyer-Ramien (2019) considers generation Z as the digital generation as a source of new ideas for corporate entrepreneurial activities and practices.…”
Section: Generation Z's Perspectivesmentioning
confidence: 99%